Wolf GPS Location Data - DeMars, Craig A.; Boutin, Stan (Dryad Digital Repository, 2017)
csv file containing GPS location data of wolves from northeast British Columbia. Note that data have been cleaned as per the methods outlines in the Journal of Animal Ecology paper.